Arsenic content in arable land of the Ząbkowice district = Zawartość arsenu w gruntach ornych powiatu ząbkowickiego - Kaszubkiewicz, Jarosław; Pora, Ewa; Kawałko, Dorota; Jezierski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study was to determine the content of arsenic in soils used for agriculture in the Ząbkowicki district. The content of arsenic in collected soil samples ranged 1.1-569.5 mg x kg-1. The standard for arable lands of Group B has been exceeded in 24 out of 231 test points.
Keywords: arsen; grunty orne; Ząbkowice (okręg); arsenic; arable land; Ząbkowicki district